Perencanaan Jaringan In-Building Coverage Di Gedung X - Sinka Wilyanti; Mauludi Manfaluthy; Drama Wicaksono (Prosiding Seminar Nasional Teknoka, 2019)
At present, the need for mobile communication is growing rapidly, with the increase in cellular phone users and also the increase of skyscrapers with construction that inhibits cellular signals for penetration into the building. This causes disruption in communication in high rise buildings, for that we need a solution to overcome these problems. In-Building Coverage will be a solution to this problem, using the path loss slope model that has been widely used in planning for in-building coverage. Antennas will be distributed to each floor of the building, so that the signal emitted by the antenna can reach more than 95% of the building area or in accordance with an agreement between the parties concerned. The signal emitted by the antenna is certainly influenced by the link budget of each antenna. The antenna reception power will be measured by a mobile phone installed with Tems Pocket software as well as a walktest method using a mobile phone and a laptop installed with Tems Investigation software to see whether the signal emitted meets the standards of the cellular operator. From the results of tests in the field, there was no disruption in cellular communication in the building. Test results on the Semi Basement floor obtained an average RSCP value of -48 dBm, on the 6th floor an average RSCP value of -52 dBm was obtained and on the 12th floor an average RSCP value of -45 dBm was obtained.